2016
DOI: 10.1186/s40064-016-2699-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of climate change awareness level in upper Nyakach Division, Kisumu County, Kenya

Abstract: Improving the understanding of climate change awareness is one of the top priorities in climate change research. While the African continent is among the regions with the highest vulnerability to climate change, research on climate knowledge and awareness is lacking. Kenya is already grappling with the impacts of climate change, which are projected to increase in a non-linear and non-predictable manner. This study sought to determine climate change awareness levels among households residing in Upper Nyakach Di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 18 publications
4
40
0
Order By: Relevance
“…In some studies, male farmers were reported to be better at adapting to CC. A higher likeliness to undertake adaptation practices was found among male farmers in Ethiopia [65], and a higher awareness of CC was found among male farmers in Kenya [84]. However, in a Pakistan study, female farmers were found to be better at using adaptation practices and had a higher level of food security [39].…”
Section: Social Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, male farmers were reported to be better at adapting to CC. A higher likeliness to undertake adaptation practices was found among male farmers in Ethiopia [65], and a higher awareness of CC was found among male farmers in Kenya [84]. However, in a Pakistan study, female farmers were found to be better at using adaptation practices and had a higher level of food security [39].…”
Section: Social Variablesmentioning
confidence: 99%
“…A study on farmer use of CC adaptation practices in Pakistan revealed that farmers with higher education are better at adjusting sowing time, using a drought-tolerant crop, and practicing crop-shifting, and these practices have resulted in higher food security [39]. Another study in Pakistan [67] and one in Kenya [84] that assessed farmer awareness of CC also found a positive effect of education on adaptation ability. Similarly, a study in Ethiopia found that education positively affects the probability of farmers adapting to CC via soil conservation and changing planting dates [65].…”
Section: Social Variablesmentioning
confidence: 99%
“…Again, we found that this predictor had not been reported as a significant predictor of climate change awareness in the developed countries [18]. However, survey studies conducted in many developing countries-especially in tropical agroclimatic zones, such as Bangladesh and Kenya-household income is a very strong predictor of climate literacy [19,20,64,65]. This may be attributed to the fact that high-income individuals and families can afford means to combat extreme hot and cold temperatures (through better heating and air conditioning facilities) and often dwell in areas with better green infrastructures.…”
Section: Discussionmentioning
confidence: 74%
“…Global warming becomes a concern all over the world because of intolerable mounting proportion of greenhouse gases in the atmosphere. This is partly attributed, among others, to burning fossil fuel, industrial activities, land use change and clearing forest (Ajuang et al, 2016;Elum, Modise, & Marr, 2016). Though there is an ontological debate on climate change or about its existence, temperature increase becomes unequivocal (Aizebeokhai, 2009;Hunt & Watkiss, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The trend is projected to rise than ever (Rahmstorf, Foster, & Cahill, 2017). Evidences show that this figure could rise to 3 °C by the end of the 21 st century unless it is mitigated beforehand (Ajuang et al, 2016). Climate change and subsequent global warming pose serious consequences on biodiversity and have proved to have intricate short and long-term consequences on the world population (Huq et al, 2015).…”
Section: Introductionmentioning
confidence: 99%